2019
DOI: 10.3390/ijerph17010108
|View full text |Cite
|
Sign up to set email alerts
|

Greenness Availability and Respiratory Health in a Population of Urbanised Children in North-Western Italy

Abstract: Paediatric Asthma contributes in paediatric global burden of diseases, as the most common chronic disease in children. Children are exposed to many environmental risk-factors, able to determine or worsen respiratory diseases, and contributing to asthma and asthma-like symptoms increases, especially in metropolitan areas. In urban settings, surrounding vegetation (greenness) may provide important benefits to health, including the promotion of physical activity and the mitigation of air and noise pollution. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Exposure to greenspace has, on the other hand, been associated with beneficial health effects such as reduced risk of mortality, diabetes, and high blood pressure [ 7 ]. However, effects of greenness on asthma and allergies are less clear [ 8 , 9 , 10 , 11 ]. Some studies have indicated decreased respiratory morbidity in adulthood due to living near green areas [ 7 , 12 , 13 , 14 ] while the effects of residential greenness on childhood allergic rhinitis and aeroallergen sensitization have depended on the region [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to greenspace has, on the other hand, been associated with beneficial health effects such as reduced risk of mortality, diabetes, and high blood pressure [ 7 ]. However, effects of greenness on asthma and allergies are less clear [ 8 , 9 , 10 , 11 ]. Some studies have indicated decreased respiratory morbidity in adulthood due to living near green areas [ 7 , 12 , 13 , 14 ] while the effects of residential greenness on childhood allergic rhinitis and aeroallergen sensitization have depended on the region [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental exposures to traffic-related air pollution, fungi, second-hand tobacco smoke, and aeroallergens, in combination with genetic predisposition and early life exposure to antibiotics, are major risk factors for developing and exacerbating allergic and non-allergic asthma (Flamant-Hulin et al 2013;Dannemiller et al 2016;Liu et al 2016;Tétreault et al 2016; Khreis et al 2017;Papi et al 2018;Guilbert et al 2018;Eguiluz-Gracia et al 2019;Murrison et al 2019;Parmes et al 2020;Buteau et al 2020;Patrick et al 2020). Vegetation may have the potential to mitigate some of these harmful environmental exposures and could therefore protect against asthma and other respiratory conditions (Tischer et al 2017;Squillacioti et al 2019;Fuertes et al 2020). For instance, urban green spaces may mitigate outdoor air pollution and hereby prevent asthma exacerbations (Markevych et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the future, additional analyses on urban settings, such as greyness/greenness quantification [46], may be helpful in driving new preventive strategies related to urban management, for outdoor workers and the general population.…”
Section: Discussionmentioning
confidence: 99%